Salivary chromogranin A levels relate to fatigability after waking up - Kentaro Taniguchi; Naoya Okumura; Naoya Jinno; Akitoshi Seiyama; Akito Shimouchi (MethodsX, 2025)
This study aimed to assess fatigue using a noninvasive, quantitative, and simple method using salivary chromogranin A (CgA). In total, 171 adults participated in this study. We used the Cornell Medical Index (CMI) as a questionnaire that included a fatigability section. The high-fatigability group had significantly (p < 0.01, d = 0.21) lower levels of salivary CgA after waking up than those of the low-fatigability group. Before sleep, participants with high stress on the musculoskeletal system (CMI E, p = 0.008, d = 0.18), skin (CMI F, p = 0.017, d = 0.16), nervous system (CMI G, p = 0.019, d = 0.16), habit (CMI L, p = 0.028, d = 0.16), sensitivity (CMI P, p = 0.022, d = 0.16), and anger (CMI Q, p = 0.011, d = 0.16) had significantly lower CgA levels than those of low stress. In conclusion, we found that salivary CgA levels after waking up could reflect fatigability, and those before night sleep could reflect chronic physical complaints. • Assessment of Salivary CgA levels using an enzyme-linked immunosorbent assay. • Routine saliva analysis could enable allow detection of chronic fatigue or stress, leading to timely lifestyle adjustments or interventions to maintain overall well-being.